Islamic wealth management towards sustainable development: a state-of-the-art analysis - Busari, Saheed Abdullahi; Olayinka, Kazeem Akeem; Abdul Aziz, Akhtarzaitie; Zakariyah, Habeebullah (UiTM Press, 2024)
In recent times, Islamic Wealth Management (IWM) has garnered increasing attention for its potential impacts on sustainable development goals, yet its role in achieving these goals remains under-researched. This study employs an advanced analytical approach to explore the relationship between IWM and SDGs, aiming to illuminate emerging trends and address key issues. Utilizing a comprehensive methodology, the research synthesizes insights from a variety of scholarly articles, journals, and research papers over a specified timeframe. By critically analyzing existing knowledge, the study seeks to understand how IWM contributes to or challenges sustainable development. Key areas of focus include wealth distribution mechanisms, ethical investment practices, and the alignment of Islamic financial principles with SDGs. Additionally, it examines practical aspects, such as the implementation of Islamic financial instruments and the role of Islamic institutions in promoting sustainable socio-economic growth. The study also addresses contemporary challenges faced by IWM, providing a nuanced understanding of its current state and potential future paths. By highlighting both successes and obstacles, this research enriches the discourse on Islamic financial practices and the evolving landscape of global Islamic wealth management. Ultimately, the study identifies a significant interplay between IWM and sustainable development, focusing on wealth distribution, ethical investments, and practical implementation.